Effectiveness of Acceptance and Commitment-Based Parenting Training on Mothers’ Meta-Emotional Perspective and Impulsivity in Mothers of Lower Secondary School Children - Faghihi , Mohammad Saleh; Atashpour, Seyyed Hamid; Sajjadian , Ilnaz (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The aim of this study was to examine the effectiveness of acceptance and commitment-based parenting training on the meta-emotional perspective and impulsivity of mothers of lower secondary school children.Materials and Methods: This research employed a quasi-experimental design using a pretest–posttest control group format with a two-month follow-up. The statistical population consisted of mothers of elementary school children in Isfahan during the 2024–2025 academic year. Thirty participants were selected using convenience and voluntary sampling and randomly assigned to an experimental group (n = 15) and a control group (n = 15). Research instruments included the Parental Meta-Emotion Philosophy Questionnaire (Evelinike, 2006) and the Barratt Impulsiveness Scale (2004). The parenting training was conducted in eight 90-minute sessions based on the acceptance and commitment approach. Data were analyzed using repeated measures analysis of variance (ANOVA) and Bonferroni post-hoc test.Findings: The results of ANOVA indicated that acceptance and commitment-based parenting training led to a significant increase in the meta-emotional perspective and a significant decrease in impulsivity scores among mothers in the experimental group compared to the control group at both the posttest and follow-up stages. A significant interaction was found between time and group membership across all three primary variables, indicating the sustained effectiveness of the intervention.Conclusion: Acceptance and commitment-based parenting training improves psychological indicators in mothers, including enhancing the meta-emotional perspective, increasing emotional flexibility, and reducing impulsivity. Therefore, it can be employed as an effective approach in parent education programs.